2019
DOI: 10.1016/j.healthplace.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Activity spaces in studies of the environment and physical activity: A review and synthesis of implications for causality

Abstract: Activity spaces are increasingly used to understand how people interact with their environment and engage in activity but their use may raise challenges regarding causal inference. We conducted a systematic review of findings and the methodological, analytical and conceptual issues relevant to causal inference. Studies were included if they comprised a spatial summary of locations visited, assessed any part of the causal pathway between the environment, physical activity and health, and used quantitative or qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 71 publications
0
51
0
1
Order By: Relevance
“…However, there was less evidence to link local PA resources, such as recreational facilities, with body weight or hypertension . Moreover, the few examples of longitudinal evaluations of the PA environment and changes in body weight have produced null or inconsistent findings .…”
Section: Evolving Measures Of Be Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…However, there was less evidence to link local PA resources, such as recreational facilities, with body weight or hypertension . Moreover, the few examples of longitudinal evaluations of the PA environment and changes in body weight have produced null or inconsistent findings .…”
Section: Evolving Measures Of Be Exposurementioning
confidence: 99%
“…Many early home‐centric BE studies had several notable limitations with respect to their study design, measurement of the BE, and their consideration of BE–health pathways. First, the majority of early BE and health studies utilized a cross‐sectional study design, which does not allow for a causal interpretation for observed associations between the BE and health . Second, home‐centric analyses can capture the BE features and resources within an individual’s neighborhood; however, proximity does not allow one to infer usage .…”
Section: Evolving Measures Of Be Exposurementioning
confidence: 99%
“…Methods for collecting and analysing social network data have become increasingly sophisticated ( Newman, 2018 ; Scott and Carrington, 2011 ) opening new possibilities for understanding how people's health may be influenced by the complex web of social relationships. Similarly, the role of the geospatial environment has been refined, now accounting for daily mobility and exposure to multiple locations, beyond one's residential neighbourhood ( Cetateanu and Jones, 2016 ; Chaix et al, 2013 ; Cummins et al, 2007 ; Diez Roux and Mair, 2010 ; Kwan, 2009 ; Perchoux et al, 2019 ; Smith et al, 2008 ). However, social and spatial contexts are generally studied separately, using tools designed to collect data on social networks (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, activity space provides information about a person's spatial footprint, which facilitates measurement of environmental exposure. In particular, activity space-based research has for example refined our understanding of environmental influence on physical activity, diet, or obesity ( Cetateanu and Jones, 2016 ; Jia et al, 2019 ; Smith et al, 2008 ), shifting the focus from the residential neighbourhood to the multiple environments to which a person is exposed.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, activity space measured by GPS and step count by accelerometer/pedometer has been increasingly used in physical activity studies to examine the associations between environments and activity [29,30]. The spaces within which people actually move and are exposed to could explain inter-and intra-personal variations in spatial habits [29]. Hence, understanding activity space could help explain different levels of physical activity.…”
Section: Introductionmentioning
confidence: 99%